Designing Pervasive Services for Physical Hypermedia Applications - Challiol, Cecilia (2006)
In this paper we describe the design and implementation of a software substrate for building pervasive services in the context of physical hypermedia applications. We first introduce the main ideas behind physical hypermedia; next we argue that physical navigation requires some software support to improve accessibility to real world objects. We next describe an architectural framework that supports specification and deployment of pervasive services. Some simple examples of use are presented. We conclude by comparing our work with others’ and describing further work we are pursuing.